PENGARUH KUALITAS AUDIT, KEAKTIFAN KOMITE AUDIT, DAN STRUKTUR KEPEMILIKAN INSTITUSIONAL TERHADAP MANAJEMEN LABA PADA PERUSAHAAN PERTAMBANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2015-2017 - Juliana, Juliana; Meilany, Meilany; Errika, Errika; Cheria, Cheria; Wongso, Sylvia; Sitepu, Wilsa Road Betterment (UNIVERSITAS SARI MUTIARA INDONESIA, 2019)
This study aims to examine: (1) the effect of audit quality to earnings management, (2) the effect of audit committee activeness to earnings management and (3) the effect of institutional ownership structure to earnings management in mining companies listed on Indonesia Stock Exchange. This research used quantitative method and descriptive research type. The method used was purposive sampling and obtained 38 companies. Data is obtained from www.idx.co.id. The analyzed method using multiple linear regression. The research partially showed that (1) Audit Quality has effect but not significant on Earnings Management. (2) Audit Committee Activeness has effect and not significant on Earnings Management. (3) Institutional Ownership has effect and not significant on Earnings Management. The research simultaneously showed that Audit Quality, Audit Committe Activeness and Institutional Ownership have effect and not significant on Earnings Management.